Mouse Model of Small for Gestational Age Offspring with Catch-up Growth Failure and Dysregulated Glucose Metabolism in Adulthood - Hyeon Seok Moon; Hanbin Kim; Bohye Kim; Min-Seon Kim; Jae Hyun Kim; Obin Kwon (Journal of Obesity & Metabolic Syndrome, 2022)
Background: We aimed to build mouse models of small for gestational age (SGA), recapitulating failure of catch-up growth and dysregulated metabolic outcomes in adulthood. Methods: Pregnant C57BL/6 mice were given a protein-restricted diet (PRD; 6% kcal from protein) during pregnancy without (model 1) or with cross-fostering (model 2). Model 3 extended the PRD to the end of the lactation period. Model 4 changed to a 9% PRD without cross-fostering. Results: Model 1 yielded a reduced size of offspring with a poor survival rate. Model 2 improved survival but offspring showed early catch-up growth. Model 3 maintained a reduced size of offspring after weaning with a higher body mass index and blood glucose levels in adult stages. Model 4 increased the survival of the offspring while maintaining a reduced size and dysregulated glucose metabolism. Conclusion: Models 3 and 4 are suitable for studying SGA accompanying adulthood short stature and metabolic disorders.